Incertezza, precarietà, capacità di immaginazione del futuro e modernità: un confronto tra Appadurai e De Martino - Alessandro Mancuso (EtnoAntropologia)
Though apparently distanced for their temporal and historical moment, their conceptual terminology, their interlocutors and the fields of their empirical research, it is possible to get some notable parallelisms of theoretical vision between the anthropological work of De Martino and that of Appadurai. In both cases, their starting point is in fact the uncertainty of human condition and social orders, and at the heart of their theory, there stands the issue of identifying the different kinds of ethos and cultural activity which permit people to historically and existentially confront this uncertainty through establishing their belonging to a “cultural homeland” (De Martino) or forms of social imagination which shape the capacities of constructively projecting themselves into the future (Appadurai). In this article, I trace a comparison among different components of both anthropologists’ theoretical apparatus, trying not only to sketch the basic elements of their “general anthropology”, but also their interplay with their interpretation of causes, phenomenology and possible ways out of the contemporary crisis, of cognitive and ethical kind, in the capacity for imagining the future in today globalised world. In their diagnosis of the present, De Martino and Appadurai, though sharing the idea that reference to universalistic values inherited by European modernity does not provide more an adequate frame for interpretation, express divergent views about modernity, its European matrix and the ethical dispositions which grow with it.